Penggunaan Pupuk Pelengkap Cair untuk Beberapa Varietas Kedelai (Glycine max L.) - Hutajulu, Leona Listiarini; Rasyad, Aslim; Zuhry, Elza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study attempt to determine the impact of liquid foliar fertilizer (LFF) application to several soybean varieties on cropgrowth and yield components. This experiment was conducted in the Experimental Farm of the Agriculture Faculty, the University of Riau from March 2018 to May 2018 in a split-plot design with three replications. Three rates of foliar fertilizer; ie, without LFF, LFF with a concentration of 2 g.l-1of water, and LFF withconcentration of 4 g.l-1of waterwere assigned as the main plot. Five soybean varieties, namely Anjasmoro, Burangrang, Dena 1, Dega 1 and Detam 1 were used as subplot.Parameters observed were plant height, flowering date, harvesting date, dry seed weight after 15, 22 days after pollination,seed dry weight at harvest, seed growth accumulation rate, effective filling period, number of filled pods per plant, number of seeds per plant, weight of 100 seeds, and seed weight per m2. Data were analyzed by the analysis of variance then followed by Duncan's multiple range test at a level of 5% probability. The results showed a variation of several soybean varieties. There is a tendency of an increase in some yield components due to application of LFF and between low to compare higher concentration of LFF.Application of LFF as supplementary fertilizer has significant effect on plant height, flowering date, and seed weight per m2 but has no effect on other parameters. Interaction between varieties with LFF affected significantly plant hight and flowering dates in which application of LFF tended to shortened time to flower and resulted taller plant height.This indicates the important use of foliar fertilizer to improve yield and yield components of soybean varieties. Keywords : folliar fertilizer, soybean varieties, crop growth, yield components